Campus And Community Collaboration Through Greening And Tutoring In Nahornop Marsada Village - Eva Rianty Angelina Sitanggang; Loren Agustina Purba; Folpin Suandi Luaha; Putri Mawati Ndruru; Safna D. N. Simanjuntak; Erisdawati Warasi (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aimed to strengthen collaboration between a higher education institution and a village community through greening and tutoring in Nahornop Marsada Village, Pahae Jae District, North Tapanuli Regency. A participatory approach was implemented through needs identification, joint planning, program delivery, mentoring, and reflective evaluation. Data were obtained from field observations, discussions with village officials and residents, activity documentation, and evaluation notes. The results indicate that tree planting and environmental cleaning fostered shared responsibility for village environmental care, while tutoring provided an accessible learning space that encouraged children to ask questions, participate actively, and strengthen their motivation to learn. Community involvement and institutional support were decisive for implementation. However, limited time, changing weather, and schedule differences constrained continuity. Continued plant maintenance and community-based tutoring are therefore necessary to sustain the program’s benefits